PERANCANGAN PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulandari, Rina Sri (Universitas Nahdlatul Ulama Sidoarjo, 2016)
The global economic crisis led many companies especially manufacturing companies be through financial distress. Financial distress is a situation where firms in difficulty conditions before be through bankruptcy. Predictions on the financial condition important by manager, auditors, and investors to make policy decisions. The more accurate the predictions were done, the risk are guaranteed getting smaller either by companies or investors. Therefore, this study aimed to design a prediction model of financial distress companies listed on the stock exchange Indonesia. This study uses the Data Envelopment Analysis (DEA) method. DEA method used to measure the efficiency of the company. The company that inefficient indicate that the company is threatened with bankruptcy. Ratios of the company’s financial statements are used as data to be processed using the DEA method.